2022
DOI: 10.3174/ajnr.a7425
|View full text |Cite
|
Sign up to set email alerts
|

Short-Range Structural Connections Are More Severely Damaged in Early-Stage MS

Abstract: BACKGROUND AND PURPOSE: Long-range connections are more severely damaged and relevant for cognition in long-standing MS. However, the evolution of such coordinated network damage in patients with MS is unclear. We investigated whether short-and long-range structural connections sustained equal damage in early-stage MS. MATERIALS AND METHODS:Sixteen patients with early-stage MS and 17 healthy controls were scanned by high-resolution, multishell diffusion imaging on 7T MR imaging and assessed cognitively. We inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Four studies highlighted reduced ODI in WM lesions compared to NWM from HC, 16,28,31,33 while opposite findings were reported in two independent studies 25,40 . One study even indicated comparable ODI values in MS WM lesions and NWM of controls 43 . Similar incongruent results were observed when investigating ODI in WM lesions compared to NAWM 16,18,30 .…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Four studies highlighted reduced ODI in WM lesions compared to NWM from HC, 16,28,31,33 while opposite findings were reported in two independent studies 25,40 . One study even indicated comparable ODI values in MS WM lesions and NWM of controls 43 . Similar incongruent results were observed when investigating ODI in WM lesions compared to NAWM 16,18,30 .…”
Section: Resultsmentioning
confidence: 85%
“…Decreased NDI was the most consistent NODDI feature in WM lesions. Specifically, NDI showed systematic reduction within WM lesions compared to NAWM 16,18,30,38,39 and normal WM (NWM, that is WM from healthy individuals) 16,25,28,31–33,38–40,43 . Studies also reported reduced NDI values in MS NAWM compared to WM in HC.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…It may be helpful to explain that long-range connections are more likely to undergo damage in MS (24,25). At the same time, a previous study also reported that early MS is more likely to have short-range connection damage (16). Thus, pathological changes, such as specific white matter demyelination, axonal damage and degenerative degeneration, may cause the presence of extensive white matter damage and microstructural damage of different lengths of connections in MS patients.…”
Section: Discussionmentioning
confidence: 97%
“…The different lengths of connections may have other effects on brain networks, implying that damage to either type of connection may have relatively specific effects. Even though there were numerous studies have proved the impairment of brain connection based on graph analysis (12-14), only a few studies have reported that MS patients have varying degrees of impairment in both short-and long-range connections (15,16). However, it is unclear whether similar or different alteration patterns exist in NMOSD patients as in MS. Additionally, it is unknown whether the damage of different fibers may influence the structural and functional networks in two diseases.…”
Section: Introductionmentioning
confidence: 99%